An efficient dual‐band filter‐antenna design based on simplified integration methodology. Issue 6 (13th March 2019) - Tang, Jiaming; Liu, Haiwen
Abstract: In this article, a newly developed filter‐antenna synthesis and realization methodology is applied to design a planar dual‐band filtering antenna. The synthesis method is derived based on the filter synthesis theory. As a result, a coupling coefficient expression is formulized more precisely specially for the antenna matched to the filter, which is essentially different from that in filter coupling. The synthesized circuit is realized by an efficient parameters extraction process. A third‐order dual‐band filtering antenna integrated with two dual‐mode 8‐shaped resonators and a dual‐inverted‐L antenna is then implemented for example to illustrate the design procedure. The integration method facilitates an efficient and practical filter‐antenna design without complicated parameters evaluation process. Finally, the proposed filtering antenna with simple structure and controllable frequencies is developed with the use of the investigated formulations and extraction curves. The circuit is realized for 2.5/3.45‐GHz WiMAX‐band applications. The tested results agree well with the simulations, showing good passbands selectivity and out‐of‐band rejection are attained.